SISTEM INFORMASI TERINTEGRASI PELAYANAN PASIEN RAWAT JALAN PUSKESMAS PEMBANTU DESA SUKA MULYA LABANGKA-SUMBAWA - Erma Suryani; Farida Idifitriani (Universitas Teknologi Sumbawa, 2024)
The outpatient service system at the Suka Mulya Labangka Village Assistant Health Center is still carried out using conventional methods, such as when registering patients, medical records, and managing drug data, which still writes the data in the ledger and then re-input the data one by one into the computer which will be used as a report which will later be submitted to the UPT Puskesmas Labangka District, this method is considered ineffective and efficient. So this Integrated Information System was made with the aim of being able to help the Suka Mulya Labangka Village Assistant Health Center in outpatient services. This research uses a qualitative approach and software development methods using SDLC (System Development Life Circle) RAD (Rapid Application Development) model and system testing using black-box testing and using four (4) types of UML diagrams as a system modeling method, namely use case diagrams, activity diagrams, sequence diagrams, and class diagrams.